Dental Arch and Mesiodistal Crown Dimensions in Normal, Crowded, and Spaced Samples - Manar Y Abdul-Qadir (University of Mosul, College of Dentistry, 2011)
Aims: To investigate the contribution of both tooth size and dental arch dimensions to dental crowding and spacing. Materials and Methods: ninty one pairs of dental casts of subjects aged 15-25 years with Cl I molar occlusion were selected for this study. The sample was divided into 3 groups: the spaced (29 pairs), the normal (32 pairs), and the crowded (30 pairs) groups. For each pair of dental casts the following parameters were measured: individual and combined mesiodistal tooth dimensions, intercanine and intermolar widths, arch perimeter, and arch length. One way analysis of variance and Pearson correlation coefficient were used for the statistical analysis. Results: significant difference was noticed among the three groups for tooth dimension both individually and combined. The spaced group showed the smallest tooth size, while the crowded group was found to have the largest tooth size among the three groups. The crowded group showed a significantly smaller upper and lower arch widths and arch perimeter when compared with the spaced and normal groups. The spaced group showed larger upper and lower intercanine widths and upper arch perimeter when compared with the normal group, but this difference was significant only for upper intercanine width. Correlation analysis revealed that spaced group has significant correlation between the space discrepancy and the sums of 6 anterior and 12 teeth in the low-er arch. While, space discrepancy in the crowded group showed significant correlation with the sum of 12 upper teeth and upper intercanine width and with lower intercanine width and arch perimeter. Conclusions: variations in mesiodistal tooth size and dental arch dimensions do exist among crowded, spaced, and normal dental arches. These variations should be taken into consideration when choosing orthodontic treatment techniques used for resolving problems related to space discrepancy.